Use of the lyapunov stability method for policy design in a class of system dynamics models - Mohapatra P.K.J.; Mandal P.; Sharma S.K. (My University, 2025)
Policy design in system dynamics models is a complex issue. The use of the Lyapunov stability method, a very popular method in modern control theory, is highlighted in synthetically generating policy structures in a class of system dynamics models that aim at designing policies for stabilizing model response. The use of the method is demonstrated by applying it to a well-known production stock problem. © 1991 Taylor & Francis Group, LLC.